Factors Influencing the Implementation of Soil and Water Conservation in Carrot Farming in East Java, Indonesia - Ngonta, Arkanjela Girlani Merici; Hanani AR, Nuhfil; Suhartini, Suhartini (Universitas Panji Sakti, 2024)
Conservation farming is part of the effort to minimize disturbances in agriculture such as floods, landslides, damage to soil aggregates, and chemical and biological soil properties on sloping land. One of the efforts to develop horticultural farming carried out in Sumberbrantas and Wonokerso villages is mostly carried out on sloping land so it needs attention because land is one of the important production factors in farming. This study aims to analyze the factors that influence farmers' decisions in implementing conservation farming. The research was conducted on carrot farms located in Sumberbrantas and Wonokerso villages, which were determined through a probability sampling approach using a simple random sampling technique conducted in August 2023. The research sample amounted to 59 respondents who were carrot farmers in Sumberbrantas and Wonokerso villages. The variables used include socio-demographics, agricultural extension, knowledge of the importance of land conservation, knowledge of conservation farming, and knowledge of how/techniques to carry out land conservation, with the dependent variable of conservation adoption level analyzed using path analysis to determine the factors that influence farmers in implementing conservation farming. The results showed that agricultural extension variables and conservation farming knowledge directly and significantly affect the level of conservation adoption by carrot farmers in East Java. Meanwhile, socio-demographic variables (age, formal education level, farming duration, household size, and land size) directly affect conservation farming knowledge. This research highlights several important points for agricultural development and conservation. Agricultural extension programs need to be strengthened while more targeted training programs are developed. When designing these programs, it is important to consider farmers' socio-demographic factors for more effective implementation. The research findings will contribute to efforts to support agricultural sustainability in hilly areas and can serve as material for developing more comprehensive agricultural conservation efforts.